Is Modernity Secular? - Perone, Ugo (Religija ir kultūra, 2014)
This article discusses the supposedly reciprocal identity between modernity and secularisation. But this kind of identity can be asserted only if secularisation is interpreted as the origin of modernity and if the contents of modernity are seen as nothing other than an immanent translation of premodern, theological contents. This double identity misrepresents both secularity and modernity. The article suggests a definition of secularisation, which pays particular attention to the formal aspects, as the essential difference between modernity and secularisation are not so much the contents themselves but the form of their unification, the horizon which gives sense to the contents and underlines the new role of the political sphere for modernity, as it becomes the form of cultural unification. The paper also analyses modernity in its self-interpretation as an age thar breaks the continuity of tradition. The connection between modernity and secularisation is close but not causal.
Keywords: secularisation; modernity; identity; politics